Silica Xerogel Obtained by Ultrashort Laser Irradiation of Tetraethyl Orthosilicate. Issue 9 (24th February 2017) - Sansone, Maria; De Bonis, Angela; Galasso, Agostino; Santagata, Antonio; Teghil, Roberto
Abstract: The formation of an opaque solid foam was induced by the direct interaction between tetraethyl orthosilicate (TEOS) and an ultrashort femtosecond laser source(Nd:glass, 527 nm, 10 Hz, 250 fs). The product, which resulted to be a silica xerogel, was characterized by different techniques. In particular, information about the morphology was obtained by scanning and transmission electron microscopy (SEM and TEM), while the presence of different functional groups was studied through IR measurements. Since the properties of this kind of material can be improved by functionalizing it with metal nanoparticles, a palladium metal target was ablated in liquid TEOS. TEM images show that palladium was present in the form of nanoparticles and EDX measurements confirm the presence of the metal inside the silica network. Abstract : Ultrashort laser irradiation of liquids is used as a new route for the synthesis of nanostructured materials. Laser irradiation of liquid tetraethyl orthosilicate (TEOS) induces its gas‐phase decomposition, and the following condensation process allows the formation of silica xerogel.